Ursodeoxycholic Acid (UDCA) Mitigates the Host Inflammatory Response during Clostridioides difficile Infection by Altering Gut Bile Acids - Jenessa A. Winston; Alissa J. Rivera; Jingwei Cai; Rajani Thanissery; Stephanie A. Montgomery; Andrew D. Patterson; Casey M. Theriot (2020)
Clostridioides difficile infection (CDI) is associated with increasing morbidity and mortality posing an urgent threat to public health. Recurrence of CDI after successful treatment with antibiotics is high, thus necessitating discovery of novel therapeutics against this enteric pathogen. Administration of the secondary bile acid ursodeoxycholic acid (UDCA; ursodiol) inhibits the life cycles of various strains of C. difficilein vitro, suggesting that the FDA-approved formulation of UDCA, known as ursodiol, may be able to restore colonization resistance against C. difficilein vivo However, the mechanism(s) by which ursodiol is able to restore colonization resistance against C. difficile remains unknown. Here, we confirmed that ursodiol inhibits C. difficile R20291 spore germination and outgrowth, growth, and toxin activity in a dose-dependent manner in vitro In a murine model of CDI, exogenous administration of ursodiol resulted in significant alterations in the bile acid metabolome with little to no changes in gut microbial community structure. Ursodiol pretreatment resulted in attenuation of CDI pathogenesis early in the course of disease, which coincided with alterations in the cecal and colonic inflammatory transcriptome, bile acid-activated receptors nuclear farnesoid X receptor (FXR) and transmembrane G-protein-coupled membrane receptor 5 (TGR5), which are able to modulate the innate immune response through signaling pathways such as NF-κB. Although ursodiol pretreatment did not result in a consistent decrease in the C. difficile life cycle in vivo, it was able to attenuate an overly robust inflammatory response that is detrimental to the host during CDI. Ursodiol remains a viable nonantibiotic treatment and/or prevention strategy against CDI. Likewise, modulation of the host innate immune response via bile acid-activated receptors FXR and TGR5 represents a new potential treatment strategy for patients with CDI.